Fault Detection and Isolation Multi-Vehicle Unmanned Systems - Meskin, Nader; Khorasani, Khashayar (Springer New York, 2011)
Fault Detection and Isolation: Multi-Vehicle Unmanned Systems deals with the design and development of fault detection and isolation algorithms for unmanned vehicles such as spacecraft, aerial drones and other related vehicles. Addressing fault detection and isolation is a key step towards designing autonomous, fault-tolerant cooperative control of networks of unmanned systems. This book proposes a solution based on a geometric approach, and presents new theoretical findings for fault detection and isolation in Markovian jump systems. The book also: Discussesthe effects of large environmental disturbances, as well as communication channels, on unmanned systems Proposes novel solutions to difficulties like robustness issues, as well as communication channel anomalies Fault Detection and Isolation: Multi-Vehicle Unmanned Systems is an ideal book for researchers and engineers working in the fields of fault detection, as well as networks of unmanned vehicles.